Improving students' physics learning outcomes through the snowball throwing type of cooperative learning model - Sriyanto Sriyanto (Berkala Fisika Indonesia : Jurnal Ilmiah Fisika, Pembelajaran dan Aplikasinya, 2022)
Penelitian ini bertujuan untuk meningkatkan hasil belajar fisika melalui pembelajaran kooperatif tipe snowball throwing. Penelitian ini menggunakan model Penelitian Tindakan Kelas (PTK) dua siklus. Penelitian dilaksanakan pada siswa kelas XI yang mengambil kelas fisika. Siswa yang terlibat berjumlah 34 orang (24 perempuan dan 10 laki-laki). Hasil belajar siswa dinilai menggunakan instrumen tes pilihan ganda. Hasil belajar siswa dianalisis menggunakan teknik persentase. Penelitian dinyatakan berhasil apabila peningkatan rata-rata hasil belajar siswa mencapai 67 dan ketuntasan klasikal mencapai 80%. Hasil penelitian menunjukkan ada peningkatan hasil belajar siswa setelah diterapkan pembelajaran kooperatif tipe snowball throwing. Jadi, pembelajaran kooperatif tipe snowball throwing dapat meningkatkan hasil belajar fisika siswa kelas XI yang mengambil kelas fisika.Improving students' physics learning outcomes through the snowball throwing type of cooperative learning model. This study aims to improve physics learning outcomes through cooperative learning type snowball throwing. This study uses a two-cycle Class Action Research (CAR) model. The research was carried out on class XI students who took physics classes. There were 34 students involved (24 girls and 10 boys). Student learning outcomes were assessed using multiple choice test instruments. Student learning outcomes were analyzed using the percentage technique. The research is declared successful if the average increase in student learning outcomes reaches 67 and classical completeness reaches 80%. The results showed increased student learning outcomes after applying snowball throwing cooperative learning. So, cooperative learning with the type of snowball throwing can improve the physics learning outcomes of class XI students who take physics classes.